Platelets Promote Brucella abortus Monocyte Invasion by Establishing Complexes With Monocytes - Trotta, Aldana; Velásquez, Lis N.; Milillo, M. Ayelén; Delpino, M. Victoria; Rodríguez, Ana M.; Landoni, Verónica I.; Giambartolomei, Guillermo H.; Pozner, Roberto G.; Barrionuevo, Paula (Frontiers in Immunology, 2018)
Brucellosis is an infectious disease elicited by bacteria of the genus Brucella. Platelets have been extensively described as mediators of hemostasis and responsible for maintaining vascular integrity. Nevertheless, they have been recently involved in the modulation of innate and adaptive immune responses. Although many interactions have been described between B. abortus and monocytes/macrophages, the role of platelets during monocyte/macrophage infection by these bacteria remained unknown. The aim of this study was to investigate the role of platelets in the immune response against B. abortus. We first focused on the possible interactions between B. abortus and platelets. Bacteria were able to directly interact with platelets. Moreover, this interaction triggered platelet activation, measured as fibrinogen binding and P-Selectin expression. We further investigated whether platelets were involved in Brucella-mediated monocyte/macrophage early infection. The presence of platelets promoted the invasion of monocytes/macrophages by B. abortus. Moreover, platelets established complexes with infected monocytes/macrophages as a result of a carrier function elicited by platelets. We also evaluated the ability of platelets to modulate functional aspects of monocytes in the context of the infection. The presence of platelets during monocyte infection enhanced IL-1β, TNF-α, IL-8 and MCP-1 secretion while it inhibited the secretion of IL-10. At the same time, platelets increased the expression of CD54 (ICAM-1) and CD40. Furthermore, we showed that soluble factors released by B. abortus-activated platelets, such as sCD40L, PF4, PAF and thromboxane A2, were involved in CD54 induction. Overall, our results indicate that platelets can directly sense and react to B. abortus presence and modulate B. abortus-mediated infection of monocytes/macrophages increasing their pro-inflammatory capacity, which could promote the resolution of the infection.